Why Being Wrong Can Be Right: Magical Warfare Technologies and the Persistence of False Beliefs - Nunn, Nathan; Sierra, Raul Sanchez de la (American Economic Review, 2017)
Across human societies, one sees many examples of deeply rooted and widely held beliefs that are almost certainly untrue. Examples include beliefs about witchcraft, magic, ordeals, and superstitions. Why are such incorrect beliefs so prevalent and how do they persist? We consider this question through an examination of superstitions and magic associated with conflict in the Eastern Democratic Republic of the Congo. Focusing on superstitions related to bullet-proofing, we provide theory and case-study evidence showing how these incorrect beliefs persist. Although harmful at the individual-level, we show that they generate Pareto efficient outcomes that have group-level benefits.